COVID-19 and children (Journal of Health Sciences, 2021)
Most children with a proven coronavirus disease (COVID-19) infection are asymptomatic or have mild symptoms. However, a small number of children have been identified in the past 2 months with developed significant multisystem inflammatory response. All children were treated according to standard protocols. Children with this disease may require hospitalization in pediatric intensive care unit with a multisystem team approach to the disease, which includes pediatricians, infectologists, cardiologists, rheumatologists, immunologists, and epidemiologists. This extremely rare disease is curable if diagnosed in time. This rare syndrome has features in common with other pediatric inflammatory diseases including Kawasaki syndrome, staphylococcal and streptococcal toxic shock syndrome, bacterial sepsis, macrophage activation syndrome, and may present with unusual abdominal pain including elevated inflammation markers. Early recognition of this disease by a pediatrician or family doctor specialist is crucial for the timely treatment and outcome of the disease.